2006
DOI: 10.1194/jlr.m600033-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Relations of APOE promoter polymorphisms to LDL cholesterol and markers of subclinical atherosclerosis in young adults

Abstract: The common apolipoprotein E (apoE) gene (APOE) e2/e3/e4 polymorphism explains part of serum lipid variation, and polymorphisms in the APOE promoter region have been proposed to participate in the regulation of serum lipid levels within the most common APOE e3/e3 genotype group. We determined APOE 2219G/T and 1113G/C promoter genotypes and estimated APOE haplotypes in 525 participants of the Cardiovascular Risk in Young Finns Study. We studied the associations of the APOE promoter polymorphisms and their haplot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
4
10
2
Order By: Relevance
“…35 Furthermore, a recent study by Viiri and coworkers found no significant association between the APOE promoter genotypes and carotid IMT, brachial FMD or CAC within the APOE 3/ 3 carriers. 36 The present study differs from that of previous studies in that we examined the association between common APOE polymorphism and carotid IMT, brachial FMD and CAC in the youngest population studied thus far (ie, young adults aged 24-39 years). The well-known link between the APOE phenotypes and serum lipids was clear but there was no association between ultrasound markers and APOE polymorphism.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…35 Furthermore, a recent study by Viiri and coworkers found no significant association between the APOE promoter genotypes and carotid IMT, brachial FMD or CAC within the APOE 3/ 3 carriers. 36 The present study differs from that of previous studies in that we examined the association between common APOE polymorphism and carotid IMT, brachial FMD and CAC in the youngest population studied thus far (ie, young adults aged 24-39 years). The well-known link between the APOE phenotypes and serum lipids was clear but there was no association between ultrasound markers and APOE polymorphism.…”
Section: Discussioncontrasting
confidence: 49%
“…Furthermore, very little is known about whether the APOE locus affects interindividual variation of brachial FMD or CAC. 35,36 Therefore, we examined the relation of common APOE polymorphism to carotid IMT, brachial FMD and CAC in 1,188 young adults (aged 24-39 years) participating in the Cardiovascular Risk In Young Finns Study. In the same population, the lipid and lipoprotein levels as well as blood pressure were examined according to the APOE phenotypes.…”
mentioning
confidence: 99%
“…In nonsmokers, the ϩ113C-allele carriers had larger lesion areas compared with G/G, which agrees with our previous results showing higher cholesterol concentrations in C-allele carriers in a longitudinal study 8 but disagrees with the results from our functional experiments. It is central to remember that based on association analyses, it is difficult to make definite conclusions about the causality of SNPs.…”
Section: Discussioncontrasting
confidence: 35%
“…4 The common APOE 2/3/4 polymorphism, 5,6 as well as 2 promoter polymorphisms of the APOE gene, Ϫ219G/T and ϩ113G/C, and their haplotype are known to have impact on serum lipid levels. 7,8 In addition to single nucleotide polymorphisms (SNPs), the APOE gene haplotype has been shown to have clinical impact. The APOE Ϫ219G/ϩ113G/3 haplotype has previously been associated with increased risk of neuropathologically verified Alzheimer disease.…”
mentioning
confidence: 99%
“…11 Carriers of the À219G/ G-genotype had 10 -20% higher apoE plasma concentrations compared to À219T/T genotype. 12 Moreover, the À219G/T polymorphism has been reported to associate with atherogenic lipid and lipoprotein profile, 13,14 as well as with coronary atherosclerosis. 15 However, the role of these SNPs in IS and in cerebral atherosclerosis has not been studied before.…”
Section: Introductionmentioning
confidence: 99%